A chemical genetic strategy identify the PHOSTIN, a synthetic molecule that triggers phosphate starvation responses in Arabidopsis thaliana. Issue 1 (4th August 2015) - Bonnot, Clémence; Pinson, Benoît; Clément, Mathilde; Bernillon, Stéphane; Chiarenza, Serge; Kanno, Satomi; Kobayashi, Natsuko; Delannoy, Etienne; Nakanishi, Tomoko M.; Nussaume, Laurent; Desnos, Thierry
Summary: Plants display numerous strategies to cope with phosphate (Pi)‐deficiency. Despite multiple genetic studies, the molecular mechanisms of low‐Pi‐signalling remain unknown. To validate the interest of chemical genetics to investigate this pathway we discovered and analysed the effects of PHOSTIN (PSN), a drug mimicking Pi‐starvation in Arabidopsis. We assessed the effects of PSN and structural analogues on the induction of Pi‐deficiency responses in mutants and wild‐type and followed their accumulation in plants organs by high pressure liquid chromotography (HPLC) or mass‐spectrophotometry. We show that PSN is cleaved in the growth medium, releasing its active motif (PSN11), which accumulates in plants roots. Despite the overaccumulation of Pi in the roots of treated plants, PSN11 elicits both local and systemic Pi‐starvation effects. Nevertheless, albeit that the transcriptional activation of low‐Pi genes by PSN11 is lost in the phr1;phl1 double mutant, neither PHO1 nor PHO2 are required for PSN11 effects. The range of local and systemic responses to Pi‐starvation elicited, and their dependence on the PHR1/PHL1 function suggests that PSN11 affects an important and early step of Pi‐starvation signalling. Its independence from PHO1 and PHO2 suggest the existence of unknown pathway(s), showing the usefulness of PSN and chemical genetics to bring new elements to this field.